Research on the thermal performance of the condenser in a loop heat pipe anti-icing system - Zhao, Yuanyuan; Li, Guang; Dang, Chaobin; Wu, Hongqiang (Frontiers in Energy Research, 2023)
Loop Heat Pipes (LHPs) are efficient heat transfer devices, providing a highly efficient and energy-saving thermal control integrated management method for Unmanned Aerial Vehicles (UAVs) with their flexible structural design. In this paper, a conceptual design of LHP anti-icing system was proposed, using LHP to transfer waste heat to wing’s leading edge. The outer surface temperature of wing skin is one of the main indicators to measure the anti-icing effect. As a result, this paper mainly focused on the heat transfer process of the condenser section by experimental and numerical simulation methods. A stainless steel-nickel LHP was fabricated and tested at different conditions. Volume of Fluid (VOF) method and Lee model were adopted to simulate the condensation process. Results showed that increasing the heating power (from 35 W to 60 W) slowed down the condensation and lengthened the two-phase zone. However, when the angle of attack changes within the range of 0°–10°, the liquid-vapor distribution in the tube remains almost unchanged. The average error of surface temperature between experiment and simulation results is 3.6% and 2.5% for the heating power of 180 W and 60 W respectively. Additionally, because the volume of water droplets collected is the largest at the leading edge of the wing, we recommend arranging the LHP condenser tube inlet near the leading edge of the wing and increasing the density of pipe arrangement to achieve better anti-icing effect.